Movement competency in rowing: the key to an effective stroke - Legge, Natalie; Slattery, Katie; Watsford, Mark; O’Meara, Damien; Nugent, Frank (Frontiers in Sports and Active Living, 2025)
Movement competency combines fundamental patterns and movement quality that enables the confident and competent execution of activities, sports and everyday tasks. This perspectives article addresses the lack of a clear definition and guidelines relating to the sport-specific movement competency required for safe and effective rowing, particularly in the context of enhancing performance. In our opinion, movement competency should be emphasised together with the physiological and biomechanical attributes of rowing performance. Based on the literature, we have proposed the following definition, ‘sport-specific movement competency for rowers incorporates the physical attributes of mobility and stability through the shoulders, trunk, hips, knees and ankles along with the associated muscular strength and endurance’ to coordinate and execute a technically effective stroke’. Our definition highlights that rowers need to coordinate different regions of the body through appropriate joint positioning and movement patterns to safely optimise force development capacity during the stroke cycle. Examples of the mobility and stability requirements during the four main stroke phases are provided. The concept of sport-specific movement competency for rowing could provide benefits for rowing participation, technical rowing efficiency, injury prevention and performance enhancement.